2021
DOI: 10.1007/s13365-021-01030-7
|View full text |Cite
|
Sign up to set email alerts
|

A case of trigeminal neuralgia developing after a COVID-19 vaccination

Abstract: In this case, we report a patient who developed acute trigeminal neuritis after using a Pfizer-BioNtech vaccination against SARS-CoV-2. The patient was completely recovered with steroid treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 10 publications
(6 reference statements)
1
33
0
Order By: Relevance
“…Prednisolone should have been used in our case as well. Kaya and Kaya 9 described the second case in which the patient presented with right TN without facial numbness 3 days after injection. The entire face was painful, and MRI did not show a remarkable change.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Prednisolone should have been used in our case as well. Kaya and Kaya 9 described the second case in which the patient presented with right TN without facial numbness 3 days after injection. The entire face was painful, and MRI did not show a remarkable change.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of trigeminal neuropathy after coronavirus vaccination seems to be extremely rare. 8 , 9 To date, only two cases of trigeminal neuropathy have been reported after vaccination against COVID-19, one with TN without facial sensory disturbance and the other with facial sensory disturbance ( Table 1 ). Narasimhalu et al 8 reported the first case of trigeminal neuritis with cervical radiculitis that occurred 3 hours after vaccination (Pfizer-BioNtech).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…13 From the literature search, apart from our case, there are 2 additional cases of trigeminal neuralgia with COVID-19 vaccination. 14,15 Likewise, the vaccine involved in these 2 reported cases was also Cominarty. However, it is worthwhile to highlight that they were thought to be due to trigeminal neuritis, a peripheral nerve involvement as opposed to our case which showed a demyelinating lesion in the pontine region, consistent with a CNS involvement.…”
Section: Discussionmentioning
confidence: 99%